Pengaruh Iklim Organisasi terhadap Komitmen Organisasional dan Kinerja Karyawan di Rumah Sakit - Suarningsih, Ni Luh Putu; Alamsyah, Arief; Thoyib, Armanu (Universitas Brawijaya, Indonesia, 2013)
This study aimed to determine the relationship among organizational climate, organizational commitment and employees'performance in hospital. The study design was descriptive analytical survey using cross-sectional study. The respondents were 81 employees at Lawang Medika Hospital who represented both medical staffs and medical-support staffs. Organizational climate was measured by using amodified Organizational Climate Questionnaire (OCQ). Organizational commitment was measured by using a modified Organizational Commitment Questionnaire (OCQ). Performance was measured using by Hariono's questionnaire. All questionnaires used five scale of Likert. Data was analyzed using path analysis to find the relationship between organizational climate, organizational commitment and employeeperformance, which is organized by using Office Excel 2010 and SPSS for Windows 19.0 software. The results showed that organizational climate influenced both organizational commitment and employees'performance positively. Organizational commitment itself also influenced employees'performance positively. Organizational climate influenced employees' performance indirectly through organizational commitment.